Vessel Health and Preservation: The Right Approach for Vascular Access - Moureau, Nancy L. (Springer Nature, 2019)
This Open access book offers updated and revised information on vessel health and preservation (VHP), a model concept first published in poster form in 2008 and in JVA in 2012, which has received a great deal of attention, especially in the US, UK and Australia. The book presents a model and a new way of thinking applied to vascular access and administration of intravenous treatment, and shows how establishing and maintaining a route of access to the bloodstream is essential for patients in acute care today. Until now, little thought has been given to an intentional process to guide selection, insertion and management of vascular access devices (VADs) and by default actions are based on crisis management when a quickly selected VAD fails. The book details how VHP establishes a framework or pathway model for each step of the patient experience, intentionally guiding, improving and eliminating risk when possible. The evidence points to the fact that reducing fragmentation, establishing a pathway, and teaching the process to all stakeholders reduces complications with intravenous therapy, improves efficiency and diminishes cost. As such this book appeals to bedside nurses, physicians and other health professionals.